2021
DOI: 10.3390/su131810218
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sustainable Rural Tourism. The Case of Uzundere District, Erzurum, Turkey

Abstract: The Uzundere district, which is located in NE Turkey, has attractive rural tourism areas with noticeable potentials and rural tourism development activities. This paper concentrates on sustainability development of rural tourism. Sustainable tourism concentrates to conserve environmental and cultural resources and emphasizes on the responsibility of tourists and participation of local people for economic growth of the region. In this study, Delphi method is used to identify important factors for evaluating sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 63 publications
0
7
0
1
Order By: Relevance
“…For this purpose, a qualitative methodology is used, based on a Delphi analysis conducted in two rounds [61,62]. Its usefulness is based on understanding the opportunities offered by these intangible assets for local territories [63][64][65].…”
Section: Design and Samplementioning
confidence: 99%
“…For this purpose, a qualitative methodology is used, based on a Delphi analysis conducted in two rounds [61,62]. Its usefulness is based on understanding the opportunities offered by these intangible assets for local territories [63][64][65].…”
Section: Design and Samplementioning
confidence: 99%
“…Turkey focuses on climate change [ 81 ] and is interested in environmental protection and the use of renewable energy [ 43 ]. In the Black Sea region, Turkey intends to focus on the development of rural tourism [ 82 ] and ecotourism, and also on strategic initiatives for sustainable tourism, that is, planning, managing and monitoring the tourism sector through long-term sustainable approaches [ 83 ]. Turkey makes effective use of its tourism industry and, together with Bulgaria, is one of the developing countries with a stable tourism industry [ 6 ].…”
Section: Resultsmentioning
confidence: 99%
“…Davardoust, S. et al took the development of rural tourism in the Uzandel district of northeastern Turkey as an example to carry out the analysis of the sustainable development of rural tourism. The results show that rural tourism should know how to protect the environment and cultural resources and then promote their feedback in rural tourism to improve the attractiveness of the countryside for tourists [19]. Kumar, S. et al showed that infrastructure, environmental conscience, government support and financial investment would guide the development of rural tourism [20].…”
Section: ) Rural Tourismmentioning
confidence: 99%